Peningkatan Kualitas Layanan Administrasi Kependudukan di Kabupaten Pinrang: Tantangan dan Strategi Perbaikan - Wahyuddin, Wahyuddin; Nasir, Nasir; Lanontji, Muryanto (LP3M, Universitas Muhammadiyah Kendari, 2024)
This research was conducted to investigate the quality of civil registration administration services in Pinrang District, focusing on identifying existing challenges and proposing improvements to enhance public satisfaction. The main objective was to conduct a thorough analysis of civil registration services, particularly regarding delays in the issuance of Electronic Identity Cards (e-KTP) and the physical infrastructure of service centers. A qualitative approach was employed, using data collection techniques such as in-depth interviews with administrative staff and direct observations at service locations. Key informants included administrative personnel and service users. Data were analyzed descriptively to identify patterns and major findings related to service quality. The study revealed that while there has been progress in service quality, challenges such as delays, and physical infrastructure deficiencies still need to be addressed. Recommendations for optimizing administrative processes, improving infrastructure, integrating technology, and enhancing staff training aim to improve service efficiency, responsiveness, and support sustainable and inclusive development in Pinrang District.